PENGEMBANGAN WEBSITE PEMBELAJARAN MENGGUNAKAN MODEL GOLD STANDARD PROJECT BASED LEARNING - Asdar Asdar; Susalti Nur Arsyad; Sri Rahmadhanningsih; Ahmad Swandi (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Currently, teachers are required not only to be able to master the content of the subjects being taught but also to be able to develop various digital-based learning media such as websites. Currently, the majority of teachers have been able to use learning websites, but there are still very few who are able to create and manage their own learning websites. Therefore, this study aims to determine whether the application of the Gold Standard Project Based Learning (GS-PjBL) in the form of training and mentoring is able to encourage teachers to be able to develop learning websites. The implementation of GS-PjBL consists of 7 stages, namely (1) Problems and challenges, (2) Study and development, (3) Testing, (4) Role enhancement, (5) Reflection, (6) Revision, (7) Product publication. . Based on the evaluation results obtained information that there is 1 group has been able to develop and complete a learning website, and the other group has been able to make menu settings on the theme, and install and choose a theme and complete the selection of hosting services. In addition, as an evaluation material, at the end of the activity, participants also filled out a satisfaction questionnaire with the ongoing GS-PjBL model of training and mentoring activities. Based on the response analysis, participants' satisfaction above 79% is in the good category. This shows that participants are satisfied with the activities they have received even though there are some shortcomings.